Selection of Best Investment Alternatives on Vacant Land In Tanjungsari Area, Surabaya Using Highest and Best Use Analysis - Ofel Simon; Ervina Ahyudanari; Aditya Sutantio (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Aims: This study was aimed to evaluates land-use alternatives using the Highest and Best Use (HBU) analysis, the Analytic Hierarchy Process (AHP), and utility theory as the basis for decision-making. Methodology and results: The findings indicate that Alternative 3, comprising a mixed-use composition of apartments (30%), offices (20%), hotels (15%), shophouses (15%), and SOHO units (20%), is the most suitable option. This alternative achieves a balance between the highest economic productivity (Rp 38,912,373.62/m²) and Sustainability (score of 2.89). The sustainability assessment covers three main dimensions: environmental, reflected in the reduction of approximately 12.5% carbon emissions and the allocation of 10% of land area to green open space (RTH); social, shown through improved accessibility, local employment opportunities, and public comfort; and economic, demonstrated by the enhancement of property value and long-term financial feasibility. From the physical aspect, attention should be given to soil type and drainage conditions on the site. Regulatory risks, initially categorized as high, can be minimized to a low level through the fulfilment of technical documentation and intensive coordination with relevant agencies (DPM PTSP, DLH, Department of Transportation, and others). Sensitivity analysis further identifies occupancy rates as the key determinant of financial success. Conclusion, significance and impact study: From the results of this study, it can be concluded that the best alternative is alternative 3 due to its high sustainability value. Not only alternative 3, but alternative 5 can also be considered due to its high sustainability value.